Navigating Survival: A Phenomenological Exploration of Families Caring for Schizophrenia Patients During Pandemic - Ilmy, Shofi Khaqul; Windarwati, Heni Dwi; Laras Ati, Niken Asih; Sulaksono, Ari Dwi (Universitas Pelita Harapan, 2025)
The role of the family in caring for individuals with schizophrenia is crucial, particularly in providing emotional support, monitoring treatment, and assisting with daily activities. This involvement inevitably leads to care burden, which can result in inadequate care during the pandemic. This study aimed to explore how families adapted to caring for a family member with schizophrenia during the pandemic. This qualitative study employed a phenomenological approach and was conducted in East Java, Indonesia. The participants included seven family members who provided care for individuals with schizophrenia within their households; none of the participants were related to each other. Data were collected through semi-structured, in-depth interviews and analyzed using interpretative phenomenological analysis (IPA). Four main themes were found by the thematic analysis, including: 1) Feeling an excessive burden of caring; 2) Hoping for the recovery of schizophrenia patient; 3) A sense of responsibility to continue caring for schizophrenia patient (core theme); 4) Trying to survive in caring for schizophrenia patient during the pandemic. The findings suggest that nurses can help alleviate family caregiving burdens through targeted interventions such as Community Mental Health Nursing and Psychosocial Mental Health Support, crucial strategies for maintaining family well-being and preventing patient relapse.